Електромагнітно сумісні сенсори на L-, С-негатронах - Філинюк, М. А.; Лазарєв, О. О.; Бондарюк, Д. В.; Ліщинська, Л. Б. (Харьковский национальный университет радиоэлектроники, 2015)
Created and tested circuit of frequency sensors based on L- and C-negatrons, shown that the negative capacitance and inductance will increase the sensitivity of the sensors in 3-5 times, and the presence of negative active resistance of C-negatron provides autogenerating and simplifies circuit implementation.
Keywords: Частотні сенсори; аналогові сенсори